Analisis potensi subsektor unggulan di Kabupaten Kediri, Provinsi Jawa Timur - Hidayah, Ana Chusniatul; Sumanto, Agus (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Along with the enactment of regional autonomy as stated in Laws No. 32 and 33 of 2004, each region is expected to be able to utilize its potential to the fullest. The direction of development that is in line with its potential will make it easier for the region to achieve the desired development. The purpose of this study was to analyze the leading sub-sectors to increase the economic growth of Kediri Regency. The data used is in the form of GRDP of Kediri Regency and East Java Province in 2016-2020. This research uses LQ and Shift Share analysis. Based on the research results, there are 4 dominant sub-sectors in the agricultural sector and 4 dominant sub-sectors in the industrial sector. The results of the shift share analysis by looking at the regional share indicators, there are 2 agricultural sub-sectors and 4 competitive industrial sub-sectors. So, the results of the combination of LQ and shiftshare analysis show that there are superior and competitive sub-sectors in Kediri Regency, namely the plantation crops sub-sector, livestock, horticultural crops in the agricultural sector, and the food & beverage industry sub-sector and paper & paper goods industry in the processing industry sector. Then, the results of the trend analysis of the agricultural and industrial sectors in Kediri Regency both have a positive trend.